1999
DOI: 10.1111/j.1528-1157.1999.tb01590.x
|View full text |Cite
|
Sign up to set email alerts
|

Callosotomy for Epilepsy After West Syndrome

Abstract: Summary:Purpose: To analyze the results of callosotomy in 17 children with symptomatic generalized epilepsy after West syndrome, according to the different seizure types and surgical procedures, to define selection criteria for candidates to callosotomy.Methods: Callosotomy was performed in two successive stages. Partial callosotomy, anterior in 13 and posterior in three, was followed by completion in 14 cases in all but four patients (complete callosotomy in one stage in one, no completion in three). All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 30 publications
2
95
2
Order By: Relevance
“…28 For example, complete corpus callosotomy is more efficient than partial callosotomy in children after West syndrome and with bihemispheric malformations of cortical development. 12,20 Spencer et al 27,28 showed a 68% seizure control rate after complete callosotomy for tonic-clonic seizures and a 57% seizure control rate for tonic seizures. Of the patients in whom anterior callosotomy failed, 60 and 50% had improved seizure outcomes after complete callosotomy for tonic-clonic and tonic seizures, respectively.…”
Section: Extent Of Callosal Resectionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 For example, complete corpus callosotomy is more efficient than partial callosotomy in children after West syndrome and with bihemispheric malformations of cortical development. 12,20 Spencer et al 27,28 showed a 68% seizure control rate after complete callosotomy for tonic-clonic seizures and a 57% seizure control rate for tonic seizures. Of the patients in whom anterior callosotomy failed, 60 and 50% had improved seizure outcomes after complete callosotomy for tonic-clonic and tonic seizures, respectively.…”
Section: Extent Of Callosal Resectionmentioning
confidence: 99%
“…16 It has been suggested that interhemispheric communication is not impaired in cases in which the corpus callosum is absent early in life, whether in the setting of callosal agenesis or due to early callosotomy. 12,15,20 Total callosotomy performed before puberty is not followed by permanent deficits of disconnection syndromes; instead, greater cognitive and social gains may be seen in these children. 14,24 Our results show that patients in both callosotomy groups achieved improved seizure control with 80% of patients in the partial callosotomy group and 87.5% in the complete callosotomy group showing durable long-term atonic seizure control.…”
Section: Extent Of Callosal Resectionmentioning
confidence: 99%
“…Some patients especially younger than 10 years of age do not experience these disconnection syndromes after total callosotomy. (Lassonde, Sauerwein et al 1991;Lassonde and Sauerwein 1997;Rougier, Claverie et al 1997;Sauerwein and Lassonde 1997;Pinard, Delalande et al 1999;Rathore, Abraham et al 2007) The callosal connection and bihemispheric connection are known to be completed at the age of 10 or 11 years. Therefore, early functional absence of callosal connections may lead to development alteration and selective reinforcement of the connection that are normally reinforced in usual circumstances.…”
Section: Morbiditymentioning
confidence: 99%
“…(Tanriverdi, Olivier et al 2009) Pinard et al showed better outcome with total callosotomy in drop attacks among pediatric West syndrome cases. (Pinard, Delalande et al 1999) Most patients being candidates of callosotomy experience multitude of seizure types. Therefore, it is feasible to analyze the outcome by the seizure types.…”
Section: Outcomementioning
confidence: 99%
“…[21][22][23] Dandy completed the first case in 1931, when he sectioned the corpus callosum during resection of a cavum cyst in a 4-year-old boy and unintentionally freed him of a seizure disorder.6 A formal description of the procedure came from Van Wagenen and Herrin in 1940, when they reported its use in 10 patients with clinically refractory epilepsy.33 Since then, the procedure has been employed for drop attacks, atonic seizures, tonic-clonic seizures, Lennox-Gastaut syndrome, and recurrent status epilepticus. …”
mentioning
confidence: 99%